HUBUNGAN SINDROM METABOLIK DENGAN NON-ALCOHOLIC FATTY LIVER DISEASE (NAFLD) - Simanjuntak, Samuel; G.U Simanjuntak, Salomo; Pasaribu, Sumihar (Jurnal Kedokteran Methodist, 2022)
Background: NAFLD is a chronic liver disorder characterized by macrovesicular (fat) steatosis but does not consume alcohol. Currently the prevalence of NAFLD has increased in various countries, both developed and developing countries, comparable to the Metabolic Syndrome. This is related to the process of the occurrence of NAFLD which has a close relationship with one or more criteria for Metabolic Syndrome, namely obesity, hyperinsulinemia, insulin resistance, Diabetes Mellitus, hypertriglyceridemia and hypertension. Methods: In this research, the research method used is literature study. Data obtained from secondary data using documentation techniques. Data documentation is based on journals related to research variables. Result: Based on a literature study, eight journals were found related to the relationship between Metabolic Syndrome and NAFLD. Conclusion: There is a relationship between Metabolic Syndrome (Diabetes Mellitus, dyslipidemia, hypertension and obesity) with NAFLD.